2012
DOI: 10.1111/j.1463-1326.2012.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of vildagliptin as add‐on therapy to metformin in Chinese patients with type 2 diabetes mellitus

Abstract: Vildagliptin as add-on therapy to metformin improved glycaemic control and was well tolerated in Chinese patients who were inadequately controlled by metformin only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 28 publications
19
63
0
Order By: Relevance
“…The mean change from baseline in HbA1c after 24 weeks treatment with vildagliptin alone and vildagliptin with metformin was similar to that reported in various RCTs for vildagliptin [8][9][10] and vildagliptin +metformin. [13][14][15] These findings support the results from RCTs, where the magnitude of HbA1c reductions with vildagliptin 16 and vildagliptin+metformin was greater in patients with higher baseline HbA1c. 17 Approximately, 16.8% patients reached the HbA1c target value of ≤6.5% and 44.6% patients reached the HbA1c target value of ≤7% with vildagliptin as monotherapy suggesting a good glycemic control in 24 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…The mean change from baseline in HbA1c after 24 weeks treatment with vildagliptin alone and vildagliptin with metformin was similar to that reported in various RCTs for vildagliptin [8][9][10] and vildagliptin +metformin. [13][14][15] These findings support the results from RCTs, where the magnitude of HbA1c reductions with vildagliptin 16 and vildagliptin+metformin was greater in patients with higher baseline HbA1c. 17 Approximately, 16.8% patients reached the HbA1c target value of ≤6.5% and 44.6% patients reached the HbA1c target value of ≤7% with vildagliptin as monotherapy suggesting a good glycemic control in 24 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the patients on metformin and vildagliptin combination showed a significant decline in , [9] who demonstrated significant decrease in FBS and PPBS levels, and Pan et al [10] who showed metformin and vildagliptin combination to significantly reduce fasting blood glucose (FBG) levels (P < 0.001) at 24 weeks when compared with metformin placebo.…”
Section: Discussionmentioning
confidence: 83%
“…Our results are in concurrence with Bosi et al, Pan et al, and Ved and Shah. [9,10,18] Bosi et al [9] evaluated the efficacy and safety of vildagliptin when added to metformin is well tolerated and produces clinically meaningful, dose-related decreases in A1C and FBS. Adverse events were reported by 65%.…”
Section: Discussionmentioning
confidence: 99%
“…Four abstracts that had been included in the previous analysis were replaced by full-text publications. In total,19 studies were included in the base case analysis at 24-weeks ± 6 weeks [7,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table S2) and a further 4 were eligible for the sensitivity analysis due to timeframe (± 8 weeks) and quality issues (Table S4). Of the 15 studies reporting data at the 52-week time point, 8 were included in the base case analysis [8,[42][43][44][45][46][47][48] (Table S3) with the remaining 7 assessed in the sensitivity analysis for the same reasons (timeframe and quality issues) (Table S4).…”
Section: Systematic Review Search Resultsmentioning
confidence: 99%